FREQUENCY OF INCIDENTALLY DIAGNOSED PROSTATE CARCINOMA IN TRANSURETHRALLY RESECTED PROSTATE SPECIMENS - Khan, Mir Attaullah; Shah, Hamid Ullah; Gul, Meena; Qayyum, Abdul (Journal of Postgraduate Medical Institute, 2017)
Objectives: To determine the frequency of incidentally diagnosed carcinoma prostate in prostatic specimens removed by transurethral approach for benign prostatic hyperplasia. Methodology: This was a retrospective study conducted from January 2011 to December 2015 on 450 specimens of transurethral prostatectomy performed for benign prostate hyperplasia. Specimens were handled in histopathology department of Lady Reading Hospital Peshawar. All consecutive transurethral prostatectomy specimens received from Lady Reading Hospital or outside, were included in the study. Patients with elevated prostate specific antigen, abnormal digital rectal examination and already diagnosed prostate cancer were excluded. Total weight of specimens, presence of prostatic carcinoma in the tissue, Gleason's scores and volume of the cancer in percentage were recorded. Hematoxylin and Eosin stains were used for staining purpose. Results: A total of 450 specimens were received. Mean age of the patients was 55 ±8 years ranging from 43-85 years. Out of these 450 specimens 8 specimens (1.8%) were found incidentally to have prostatic cancer. Gleason score ranged from 6 to 7. Six specimens had T1a while two had T1b cancer. Age of all of the patients having incidental cancer was above 60 years. Conclusion: Incidental prostate cancer continues to be present in transurethral specimens specifically of elderly patients. Therefore specimens of such patients should be dealt with care both grossly and microscopically.